Thoracic spinal cord injury without vertebral body fracture or malalignment: A case report and preview of the literature - (:unkn) unknown (My University, 2009)
Bu çalışmada, vertebral cisim kırığı veya dizilim bozukluğu olmaksızın torosik spinal kord yaralanması olan bir olgu sunulmuştur. Bu hasta, endüstriyel ezici bir kazaya maruz kalmıştır. Kemik lezyon veya ligamentöz yaralanma olmaksızın spinal kord yaralanması, erişkinlerde çok nadir bir durumdur. Manyetik rezonans görüntülerin incelenmesi T10-12 düzeyinde ligamentöz harabiyet olmaksızın spinal kord kontüzyonu olduğunu ortaya koymuştur. Benzer olarak, kompüterize tomografide omurgada kemik yapıda bir hasar olmadığı belirlenmiştir. Sonuç olarak, erişkin omurga travması olgularında vertebral cisim kırığı veya dizilim bozukluğu olmaksızın, spinal kord yaralanması olabileceği akılda tutulmalıdır.

A case of thoracic spinal cord injury without vertebral body fracture or malalignment has been reported. The patient was involved in an industrial compression accident. Spinal cord injury without bone lesion or any ligamentous injury is a rare condition in adut population. Evaluation of magnetic resonance images showed spinal cord contusion on T10-12 with no evidence of ligamentous damage. Similarly, no evidence of bone damage to the spine was found on the plain and computed tomography. In conclusion, it should be kept in mind that in trauma case, spinal cord injury may occur without any vertebral body fracture or malalignment.
Vertebral cisim kırığı veya yanlış dizilim olmaksızın ortaya çıkan torasik spinal kord yaralanması: Olgu sunumu ve literatürün gözden geçirilmesi
Keywords: Cerrahi